Química supramolecular: uma jornada através da cristalização de 1,3,5-tris(pirazolil)benzenos e aminoisoxazóis e gelificação de n-fenilestearamidas - Meyer, Alexandre Robison (2017)
This work presents the study of intermolecular interactions involved in the formation of molecular crystals and supramolecular gels. The compounds 3-amino-4-halo-5-methylisoxazoles and 1,3,5-Tris(pirazolyl)benzenes were synthesized and used as molecular models in the study of crystal packing. For the study of supramolecular gels were synthesized N-phenilestearamides. The crystal packing was evaluated by several tools including, X-ray diffraction, theoretical calculations, molecular electrostatic potential maps and quantum theory of atoms in molecules. The interaction energy of the central molecule and theirs neighbors in the supramolecular cluster was determined. This determination was realized by theoretical calculations at the MP2/cc-pVTZ level of theory for the interactions present in the crystal packing of 3-amino-4-halo-5-methylisoxazoles and ωB97X-D/cc-pVDZ for the interactions of 1,3,5-Tris(pirazolyl)benzenes. These interactions were hierarchized according to its energy and crystallization mechanisms were proposed. The gelation properties of the N-phenilestearamides were evaluated in several organic solvents. The supramolecular gels were characterized by rheology. Nuclear magnetic resonance experiments were employed to evaluate the interactions involved in the gelation process. The crystal packing analyses of the 3-amino-4-halo-5-methylisoxazoles showed that the change of the halogen atom changes deeply the crystal packing. In these compounds firstly occurs the formation of supramolecular dimers connected by NH∙∙∙N hydrogen bonds that are connected by π∙∙∙π interactions forming 1D chains. In the connection between the chains occurs a competition between a second π∙∙∙π interaction and CH∙∙∙π interactions. This competition is the great responsible for the changes in the supramolecular structure of these compounds. The halogen insertion also affects the molecular and supramolecular structure of the 1,3,5-Tris(pirazolyl)benzenes. Two molecular conformations were adopted by these compounds, a first in a calyx form and a second twisted. This adopted conformation affects deeply the crystal packing. So on, in the first molecular association the molecules in the calyx form associate forming 1D chains, already the molecules in the twisted form forms supramolecular dimers. These changes are propagated along the next associations forming totally different supramolecular structures. A second factor that influences in the crystal packing of these compounds is the interactions that govern the first molecular association. This generally occurs between the sites with the greatest electrostatic potential. The CH∙∙∙N interaction is the strongest for the majority of the compounds. Being overpowered only by I∙∙∙N interactions, when the molecule is iodated, or by π∙∙∙π interactions, when there are rings with great difference in the electrostatic potential. In relation to the supramolecular gels, the substituents of the phenyl in the N-phenilestearamides (H, methyl, acethyl) did not cause great changes in the gelation of these compounds. Being gelled both polar and non-polar solvents. However the compound with H substituent showed the minor values of critical gelation concentration, and may be considered a supergelator in some cases. The rheological data proves the gel behavior. And the nuclear magnetic resonance showed that the hydrogen bonds together with van der Waals interactions are responsible by the gelation of the solvents.